Manajemen Strategi Peningkatan Mutu Pendidikan di SD Islam An-Nur Kota Serang Banten - Dedy Yansyah; Siti Patimah; Andi Warisno; Nurul Hidayati Murtafiah (Journal on Education, 2024)
This exploration intends to portray the Administration Methodology for Working on the Nature of Sekolah Training. The examination strategy utilized is a subjective illustrative technique. Information assortment procedures were helped out through meetings, perception and documentation studies. The consequences of the exploration show that the execution of Technique The board at SD Islam An Nur Kota Serang Banten Regime was brought out through: a drafting group comprising of the madrasa head, delegate head, 2 instructors and a madrasa council. The plan of the vision and mission is arranged utilizing short and clear sentences so realizing the normal benchmarks is simple. Examination of ecological open doors and dangers is examined in inward discussions as a reason for deciding strategy, yet has not been arranged in composed records. Long haul plans are ready for the initial 4 years, while yearly plans are ready in a deliberate way toward the start of every year. Expanding compelling, precise and productive learning keeps on being done by opening Bilingual classes directed by proficient staff from LBB English Town "Mahesa" Pare, Kediri Regime. Working on the nature of instructors by getting ready showing devices as indicated by the 2013 Educational plan and KTSP, MGMP for each subject and studios. This educational plan program is remembered for the 2013 educational plan idea by adding a commonplace educational plan as one of the unrivaled madrasa programs. Understudy programs incorporate ability interest improvement projects and character training programs. The framework program has sufficient foundation with nonstop control and filing so the foundation stays in great shape and prepared for use. Every one of the endeavors made can make it more straightforward for Incorporated SD Islam An Nur Kota Serang Banten to work on the nature of schooling.